mRNA coding for neurotransmitter receptors in a human astrocytoma. - Matute, C (1992)
Electrophysiological techniques and Xenopus oocytes were used to study the expression of neurotransmitter receptors encoded by mRNAs isolated from three human glioma cell lines. Oocytes injected with mRNAs from two glioblastoma cell lines did not show electrical responses to the various neurotransmitters tested. In contrast, oocytes injected with mRNA from an astrocytoma cell line (R-111) acquired acetylcholine and glutamate receptors as well as a small number of N-methyl-D-aspartate (NMDA) receptors. Acetylcholine elicited oscillatory Cl- currents that were abolished by muscarinic antagonists. The muscarinic receptors are coupled to the inositol phosphate-Ca2+ receptor-channel coupling system. Glutamate and its analogs kainate, quisqualate, and alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid induced smooth currents. The non-NMDA responses were potently blocked by 6,7-dinitroquinoxaline-2,3 dione. Our results show that human astrocytoma cells contain mRNAs coding for functional acetylcholine and glutamate receptors that have properties similar to those of neurons. In contrast, human glioblastoma cells lacked those mRNAs. These differences might be useful for the development of new diagnostic and therapeutic procedures.